Factors Influencing the Application of Agricultural Technology in Veteran Jaya Village, Martapura District, Ogan Komering Ulu Timur Regency - Yunita, Yunita; Efrianti, Rini; Sari, Yunita; Novayanti, Novayanti (ITScience (Information Technology and Science), 2024)
This study explains the problems in terms of the factors that influence the application of agricultural technology in Veteran Jaya Village, Martapura District, East OKU Regency. This study emphasizes the role of farmer groups in the application of agricultural technology in Veteran Jaya Village, Martapura District, East OKU Regency, especially in rain-fed rice farming. The purpose of this study was to describe the factors that influence the application of agricultural technology in Veteran Jaya Village, Martapura District, East OKU Regency. The type of research used in this study is the quantitative descriptive method (Valeriana et al., 2020). The data obtained from the study population sample were analyzed according to the statistical method used and then interpreted. Based on the results of the analysis, it can be concluded that the factors (X1) age of farmers, (X2) length of education, (X3) land area, (X4) have a significant effect on farmers' decisions to apply agricultural technology in Veteran Jaya Village, Martapura District, East OKU Regency. The most influential factor in the application of agricultural technology in Veteran Jaya Village, Martapura District, East OKU Regency is the experience of farming rice fields with a standard value of the partial regression coefficient of 6.049.